PENINGKATAN NILAI-NILAI KARAKTER ANAK USIA DINI MELALUI KESENIAN REYOG PONOROGO - Dian Kristiana (Universitas Muhammadiyah Ponorogo, 2017)
The aims of this research are to improve the value of early childhood characters and to describe the increase in the values of the character through the arts reyog Ponorogo in BA Aisyiyah Keniten Ponorogo. This research is action research, the study subjects were 30 kindergarten students in BA Aisyiyah Keniten Ponorogo. The research location is in BA Aisyiyah Keniten Ponorogo. The collection of data necessary to support the research, questionnaires, observations, and interviews. Data obtained during the investigation which lasted analyzed both quantitatively and qualitatively to obtain maximum results. The results show that through art Reyog Ponorogo increase in the values of characters in BA Aisyiyah Keniten can be improved. It can be seen from the increase in the values of the characters with respect and courtesy by 83% to 93%; collaborated character value of 80% increased to 86.7%; independence 87% increase to 96.7%, while for discipline 76.7% to 90%. For the love of God's character by 80% to 96.7%.